Structural elements of rps0 mRNA involved in the modulation of translational initiation and regulation of E. coli ribosomal protein S15. - Philippe, C (1994)
Previous experiments showed that S15 inhibits its own translation by binding to its mRNA in a region overlapping the ribosome loading site. This binding was postulated to stabilize a pseudoknot structure that exists in equilibrium with two stem-loops and to trap the ribosome on its mRNA loading site in a transitory state. In this study, we investigated the effect of mutations in the translational operator on: the binding of protein S15, the formation of the 30S/mRNA/tRNA(fMet) ternary initiation complex, the ability of S15 to inhibit the formation of this ternary complex. The results were compared to in vivo expression and repression rates. The results show that (1) the pseudoknot is required for S15 recognition and translational control; (2) mRNA and 16S rRNA efficiently compete for S15 binding and 16S rRNA suppresses the ability of S15 to inhibit the formation of the active ternary complex; (3) the ribosome binds more efficiently to the pseudoknot than to the stem-loop; (4) sequences located between nucleotides 12 to 47 of the S15 coding phase enhances the efficiency of ribosome binding in vitro; this is correlated with enhanced in vivo expression and regulation rates.